Narrative literature review: Effect of Branched-chain Amino Acids (BCAAs) on muscle hypertrophy and athletic performance - Rudnicki, Jakub; Szczepocki, Matthew; Jurek, Joanna Michalina; StefaÅ„ska, Olga (Tanjungpura Journal of Coaching Research, 2024)
Background and Study Aim. Branched-chain amino acids (BCAAs) have received considerable attention in sports science due to their potential benefits in improving athletic performance and promoting muscle recovery. BCAAs including leucine, isoleucine, and valine, are essential amino acids that are important for muscle protein physiology. To date, studies have shown positive effects of BCAAs supplementation on muscle recovery, muscle soreness, and cognitive function. Hence, with the growing popularity of using dietary supplements for optimal athletic performance, this narrative literature review aims to investigate the role and potential of BCAAs supplementation to influence muscle function and improve physical performance, while highlighting the potential benefits and side effects associated with their supplementation.Material and Methods. The current review was conducted according to PRISMA (Preferred reporting items for systematic review and meta-analysis) guidelines. Electronic databases including Web of Science (all databases), PubMed, Scopus, Google Scholar, Science Direct, were explored on June 11, 2022.Results. Based on recent evidence, BCAAs have been shown to reduce muscle damage, improve muscle recovery and repair, increase muscle protein synthesis, and maintain muscle mass during periods of energy restriction, however may also have some potential side effects such as liver damage, kidney dysfunction and negative effects on glucose metabolism.Conclusion. In conclusion, studies investigating the potential benefits of BCAAs obtained from supplementation and diet to improve athletic performance are promising due to their demonstrated effects in increasing muscle protein synthesis, reducing muscle soreness, and improving cognitive function under stress. Nevertheless, excessive supplementation should be avoided due to the potential risk of toxicity and side effects.